2009
DOI: 10.1111/j.1365-3059.2008.01939.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and biochemical changes in Brassica juncea (mustard) infected with Albugo candida (white rust)

Abstract: Components of disease reaction, including incubation period, pustule types, inoculum production and disease index (DI); and contents of protein, phenols, soluble sugars and reducing and non‐reducing sugars were investigated in cotyledonary and true leaves of six genotypes of Brassica juncea: Varuna, Kranti, EC‐399296, EC‐399299, EC‐399313 and EC‐399301, inoculated with Albugo candida. Cotyledonary leaves were examined 14 days after inoculation (d.a.i.), whereas true leaves were scored 14 and 21 d.a.i. Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 13 publications
3
14
1
Order By: Relevance
“…Surprisingly, exotic lines EC-399299, EC-399313 and EC-399301 exhibited disease reaction ranging from a moderate to a high degree of susceptibility at both stages. This is in contrast to an earlier observation at the university field experimental station at Pantnagar (northern India) where moderate visible infection with white rust at the cotyledonary leaf stage and little or almost no visible infection with this disease at the true-leaf stage was obtained (Mishra et al 2009). This may be attributed to the variation in racial composition of A. candida isolates at the two locations.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, exotic lines EC-399299, EC-399313 and EC-399301 exhibited disease reaction ranging from a moderate to a high degree of susceptibility at both stages. This is in contrast to an earlier observation at the university field experimental station at Pantnagar (northern India) where moderate visible infection with white rust at the cotyledonary leaf stage and little or almost no visible infection with this disease at the true-leaf stage was obtained (Mishra et al 2009). This may be attributed to the variation in racial composition of A. candida isolates at the two locations.…”
Section: Resultscontrasting
confidence: 99%
“…Varuna, which is amongst the oldest but is still a highly popular variety of Indian Mustard in India, exhibited the maximum ( !70%) disease index under both the stages of plant growth. This was similar to the earlier reports (Li et al 2008;Mishra et al 2009). Indigenous germplasm collections, however, showed wide variation in terms of disease reaction and exhibited moderate to high resistance.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is believed that depletion of carbohydrates enhances plant susceptibility to a pathogen infection (Morkunas and Ratajczak 2014, Bezrutczyk et al 2018, Kanwar and Jha 2018. A decrease in the content of total sugars and reducing sugars in B. juncea during progressive A. brassicae infection (Mathpal et al 2011) and Albugo candida infection (Mishra et al 2009) was reported.…”
Section: Black Spot Disease Influences Brassica Juncea Primary Metabomentioning
confidence: 99%
“…aggressiveness of race, amount of available initial inoculum, time of first appearance of the disease and prevailing weather conditions. A. candida isolates from different Brassica species/cultivar or from different geographical regions may be different in their incubation period, latent period and production of sporangia and zoospores, pustule size, shape and texture and aggressiveness (Lakra and Saharan, 1988;Gupta and Saharan, 2002;Patni et al, 2005 andMishra et al, 2009).…”
Section: Introductionmentioning
confidence: 99%